Selective antibacterial activities and storage stability of curcumin-loaded nanoliposomes prepared from bovine milk phospholipid and cholesterol - Wu, Yujie; Wang, Ke; Liu, Qinru; Liu, Xingyu; Mou, Bolin; Lai, Oi-Ming; Tan, Chin-Ping; Cheong, Ling-Zhi (Elsevier, 2022)
Present study prepared curcumin-loaded nanoliposomes using bovine milk, krill phospholipids and cholesterol; and investigated the effects of cholesterol on membrane characteristics, storage stability and antibacterial properties of the curcumin nanoliposomes. Bovine milk phospholipids which have higher saturation than krill phospholipids resulted in formation of curcumin-loaded nanoliposomes with higher encapsulation efficiency (84.78%), larger absolute value of zeta potential and vesicle size (size: 159.15 ± 5.27 nm, zeta potential: −28.3 ± 0.62 mV). Cholesterol helps to formation of a more hydrophobic, compact and tighter bilayer membrane structure which improved the storage stability of nanoliposomes under alkaline (66.25 ± 0.46%), heat (43.25 ± 0.69%) and sunlight (49.44 ± 1.78%) conditions. In addition, curcumin-loaded nanoliposomes can effectively target infectious bacteria which secrete pore-forming toxins such as Staphylococcus aureus by causing the bacterial cell wall to lysis. Findings from present work can guide future development of novel antibacterial agents for use in food preservation.